Relevant and Rigorous: Human-Centered Research and Design Education. - Hanington, Bruce M. (Design Issues)
The article discusses why an integrated approach to human-centered research and design is needed in post-secondary design education in North America. The scientific method is stated to reduce bias, increase credibility, and produce a generalizable result that can link findings with outcomes. The process-oriented model of education used at Carnegie Mellon University, which is based on the exploratory, generative, and evaluative phases of research and design, is mentioned. Topics include ethnography and design, participatory design, and testing design.